Clinical anatomy of the retrocalcaneal bursa - Kachlik, D; Baca, V; Cepelik, M; Hajek, P; Mandys, V; Musil, V; Skala, P; Stingl, J (Surgical and radiologic anatomy, 2008)
The goal of the study was to perform a detailed anatomical description of the retrocalcaneal bursa (RB). Its morphological arrangement was studied on 10 fresh and 30 embalmed lower extremities by microdissection and light microscopy. The RB was present constantly and in all the cases contained 1-2 cm long synovial fold, beginning on the upper wall of RB and distally interposed between the anterior surface of the Achilles tendon and the posterior surface of the calcaneal tuberosity. The volume of RB was 1-1.5 ml. The histological analysis confirmed that the inner surface of the superior and posterior wall of RB have been covered by unilayered synovial membrane, projecting into synovial villi of different shapes and sizes. In the ceiling of RB, delicate fascicle of skeletal muscle fibers was discovered, radiating distally into the regularly present synovial fold. The whole bottom of RB has been covered by 200-500 microm layer of fibrous cartilage into which the calcaneal tendon attached. The cartilagineous layer continued anteroproximally to cover the whole bursal surface of the calcaneal tuberosity, where the thickness of the cortical bone was reduced on mere 50 microm. The obtained results can be used in the improvement of the differential diagnostics and therapy of diagnostics and therapy of the retrocalcaneal bursitis as well as of other kinds of achillar enthesopathies and heel pain.
Keywords: Tendinopathy; Calcaneus; Foot; Bursa, Synovial; Achilles Tendon; noha (od hlezna dolů); tendinopatie; patní kost; lidé; Bursitis; Achillova šlacha; burzitida; bursa synovialis; Humans